Building and Standardizing Creative Administration of Some Iraqi Soccer Premier League 2016 – 2017 from the Players and Administrators Point of View - Mohammed, Ismael; Abedul jabar, Mohammed (Journal of Physical Education, 2018)
Building and Standardizing Creative Administration of Some Iraqi Soccer Premier League 2016 – 2017 from the Players and Administrators Point of View The aim of the research is to build and standardize the administrative creativity standard for the coaches of Iraqi Premier League clubs from the point of view of the players and managers. The tests and measurements are an essential element of the evaluation process. The research problem was identified by asking the researcher questions in order to know the level of administrative creativity of trainers. The criteria for these levels were used. The descriptive method was used in the survey method. The sample consisted of 468 players and administrators of the Iraqi League. And the researcher took the scientific steps required to obtain the scale in its final form, using the appropriate statistical means to achieve its objectives, and resulted in the researcher obtained the personality of the leadership of the administrative and composed of five areas, and then used the scale in the extraction of levels and criteria for the study, The administrative management standard consists of more than one factor , and the administrative management standard has become in its final form consists of (31) paragraphs distributed across the four scale fields. The researcher recommended strengthening administrative creativity of the trainers because of their importance in raising the level of the team.